HUBUNGAN PRODUK, HARGA, PROMOSI, DAN TEMPAT DENGAN LOYALITAS KONSUMEN PRODUK ONDULINE DI KOTA PONTIANAK - B11108097, ANGELINA CAROLIN (Jurnal Manajemen Update, 2015)
This study aims to determine the perception of custumers about the product, price, promotion, and place the Onduline product in Pontianak city. Variables used in this study is the marketing policy as a variable (X) consist of product (X1), price(X2), promotion (X3), place (X4), while loyality is variable (Y). Population in this study is a consumer Onduline product who reside in the city of pontianak. Samples taken from 100 respondents. Data used is the result of frequently asked questions and questionnaires filled by by the consumer. In data analysis, this research analysis use average score calculation research variables and correlation analysis with SPSS For Windows 16.0. Research show that emotions have a significant association was highest among the three other independent variables to the loyality of the repondent Onduline. The research finding designation that the average respondent to the Onduline roof loyalty is at a high category. Â  Keywords : Produk (X1), Price (X2), Promotion (X3), Place (X4), Loyality (Y)